Key Plant, Key Pests: Baldcypress (Taxodium distichum) - Juanita Popenoe; Caroline G Roper Warwick; Roger Kjelgren (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists and landscape professionals to help identify common pests associated with common Florida fauna. This publication, the first in the Key Plant, Key Pests Series, helps identify the most common pests found on the Baldcypress (Taxodium distichum). This publication provides information and general management recommendations for the cypress leaf beetle, fall webworm, cypress twig gall midge, mealybugs, rust mites and needle blights. https://edis.ifas.ufl.edu/ep557